A critical review of valuation studies for coral reefs and damage compensation in the Philippines - Abrina, Tara Alessandra S.; Magno, Cielo D. (Quezon City School of Economics, University of the Philippines Diliman, 2020)
In 2006, the economic valuation of Tubbataha Reef was undertaken for the purpose of calculating appropriate fines for ship grounding damages. That valuation study, Rosales (2006), prescribed that the fines should be based on the Total Economic Value (TEV; also called productivity) and restoration cost estimates. However, this approach has been shown to be incompatible with welfare-based economic foundations in legal and decision-making processes, at least in the way it has been applied in Philippine coral reef policy. The aim of this thesis is to review the ship grounding fines recommended by Rosales (2006) and its reference studies through the lens of microeconomics. Based on the review, I propose a methodology that uses (1) hard coral cover instead of area damaged; (2) willingness to pay (WTP) values for coral restoration instead of TEV; and (3) a tort law liability adjustment in order to integrate standard coral health metrics, social welfare, and remedial law in coral reef policies. This study demonstrates this methodology in the context of recalculating the fines from a ship grounding case on Tubbataha Reef in 2013. Results show that, although mean WTP values lead to a 235% increase in preferred recommended fines from Php 28M to Php 93M (2013 current prices) when the probability of the grounding is assumed at 10%, using the lower bounds of WTP values from a choice modelling reference study shows that the original fines from Rosales (2006) are not statistically different from the revised fines. Nevertheless, these revised fines are an improvement over the original fines as they include welfare economics and legal science considerations.
Thesis (Master in Development Economics) -- University of the Philippines Diliman
Keywords: Reef plants -- Valuation -- Philippines; Coral reefs and islands -- Philippines; Coral declines -- Economic aspects -- Philippines